Analyzing QoS metrics in IEEE 802.11ah networks with traffic differentiation - Arnosti, Sergio Zumpano; Borin, Juliana Freitag (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2019: Anais do XXXVII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2019.7411, 2019)
The IEEE 802.11ah is one of the most recent wireless protocols that has emerged, aiming to improve Internet of Things (IoT) devices communication. Among the 802.11ah related works that evaluate the Restricted Access Window (RAW) and others medium access control mechanisms, only a few consider Quality of Service (QoS) and the inherent traffic heterogeneity in IoT. Nevertheless, the purpose of this work is to compare two RAW scenarios, which consider two types of devices with different traffic patterns and QoS requirements. The results suggests that the increase of medium contention inside RAW slots in dense networks may be a limiting factor for providing QoS.